Barriers to Knowledge Sharing: A Case Study of Construction Companies in Surabaya - Agraprana, Andhika; Puspa Negara, Kartika; Padma Devia, Yatnanta (KnE Social Sciences, 2024)
Knowledge-sharing (KS) barriers prevent organizations from capitalizing on their skills and knowledge assets. This research aimed to investigate the main barriers to knowledge-sharing and identify the commonly used practice of the knowledgesharing process in the construction company in Surabaya. Data was collected by sending questionnaires to the top management of large contractors (Qualification B) in Surabaya. Fifty-four questionnaires were collected and considered eligible for analysis. The Relative Importance Index (RII) method was used in this research. The results showed that internet/social media, e-mail, and face-to-face interaction are commonly used for knowledge-sharing. The results also showed that the top barrier to knowledge sharing was the lack of top management support and participation. Meanwhile, the top personal barrier was difficulties in generalizing knowledge from one project to another project. This study helped to understand the main barriers to the knowledge-sharing process in construction companies and provided some practical guidance for companies to deal with these barriers. Moreover, this study helped top management to provide strategies to alleviate the barriers to knowledgesharing within their organization in order to achieve the success of construction projects. Keywords: knowledge-sharing barriers, construction industry, knowledge-sharing practices